Knowing Victims to Protect Them, A Book Review “Viktimologi: Perlindungan Korban dan Saksi” Bambang Waluyo, S.H., M.H., Sinar Grafika Jakarta, 2011, 320 pages, ISBN 978979074378 - Wijaya, Enggal Prayoga (JILS (Journal of Indonesian Legal Studies), 2021)
Understanding Victim (victim) and logi (science), Latin "victima" victims of "logos" science. Means knowledge about victims of crime. In a criminal trial the parties that play a role are the public prosecutor, judge, defendant, and legal counsel and witnesses. The victim was represented by the public prosecutor and to corroborate the usual evidence he was made a witness (victim). Often the public prosecutor acts at will by not representing the interests of the victim and ignoring the victim's protection rights. The victim was ignored because: The problem of crime cannot be understood in proportion The problem is not based on the prevailing theory Understanding the problem is not seen from the human side